Nature and Artificiality: in Search of a lost Harmony - Giuseppe De Giovanni (Agathón)
Maghreb’s desert, an eternal landscape of slow and irrational creation, or the Motya’s Salterns, geometrical landscape, logical and violent. Both landscapes capture our attention: the desert enhances nature, it is not susceptible to enduring changes and only works through a set of unrecognizable rules. Motya’s Salterns are an artificial product of scheduled changes, where man is the author of transformations driven by logical principles. In the past, the man-nature-territory relationship was a perfect harmony, where changes were not violent, but balanced, and distinguishing nature from artificiality was possible.